Effect of low-dose sodium nitrite treatment on the endogenous antioxidant capacity of yak meat during wet curing: Pros and cons. (April 2021) - Ma, Guoyuan; Wang, Zhuo; Chen, Haoyu; Yu, Qunli; Han, Ling
Abstract: This study aimed to investigate the effects of sodium nitrite treatment on antioxidant enzyme activity and free radical changes in yak meat during wet curing. The effect on superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and nitric oxide synthase (iNOS, TNOS) activity; superoxide anion (O2 − ) content and production rate; hydrogen peroxide (H2 O2 ) content; nitric oxide (NO) content; and meat hydroxyl radical (OH) inhibition ability were determined. The results showed that NaNO2 treatment effectively increased the activity of CAT, GSH-Px, and NOS (TNOS, iNOS) over the first 3, 5, and 7 days ( P < 0.01) following application, respectively, while simultaneously inhibiting the activity of SOD ( P < 0.01). In addition, NaNO2 treatment resulted in an increase in O2 − content and rate of O2 − production in meat, as well as a decrease ( P < 0.01) in H2 O2 content on the third day of curing. With the addition of NaNO2, the inhibition ability of OH first increased and then decreased, and the NO content in meat increased ( P < 0.01). The preliminary study showed that low-dose sodium nitrite could improve the endogenous antioxidant capacity of yak meat during the wet curing process, although it also had negative effects. Highlights: The role of sodium nitrite during short-term wet curing was investigated. The endogenous antioxidant capacity of yak meat was systematically investigated. The kinetics of endogenous antioxidant enzymes were analyzed. Two functions of sodium nitrite in this process: pros and cons were discovered.